Depression and Suicide Message as Seen in Chester Bennington of Linkin Park’s Selected Lyrics From 2000 (Hybrid Theory) Until 2017 (one more light) - Febrina Fitri Waskita; Raflis Raflis (Fakultas Sastra Universitas Ekasakti, 2019)
Linkin Park consists of six people, namely Chester Bennington as the vocalist, Mike Kenji Shinoda as a rapper (founder of Linkin Park), Brad Philip Delson as a guitarist, David Micheal